La emergencia de lo andino como utopía (siglo XVII) - Burga, Manuel (1990)
In this brief essay I will address two very well defined themes, both part of the same general theme, although somewhat different, about what we insist on calling the Andean Utopia. I must quickly point out that the history of this utopia, quite verifiably, is also the inconspicuous history of Peru. A history understood as a process where the essential confrontation between the Andean and the Western, the indigenous and the European, of a social, political and ideological nature, has contributed to defining the character and singularity of the national society of contemporary Peru.